PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN KELOMPOK TANI DI DESA TONOM KECAMATAN DUMOGA TIMUR KABUPATEN BOLAANG MONGONDOW (The Role of Agricultural Extension Officers in the Development of Farmers' Groups in Tonom Village Dumoga Timur District) - Injilia Vionita Kemur; Jenny Baroleh; Melsje J. Memah (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to determine the role of agricultural extension workers in the development of farmer groups in Tonom Village, Dumoga Timur District, Bolaang Mongondow Regency. This research was conducted from June to August 2022. The data used in this study were primary data were obtained from data from extension workers and farmer respondents through interviews using a questionnaire. Meanwhile, secondary data were obtained from agencies related to the research. Sampling was done by purposive sampling (deliberately) as many as 14 samples. The results show that the role of agricultural extension workers in the development of farmer groups in Tonom Village, Dumoga Timur District, Bolaang Mongondow Regency is calculated for each score of the number of questions. The role of extension workers as motivators, educators, catalysts, organizers, communicators and advisors. The results showed that the total score was 625 compared to the highest ideal score of 840 multiplied by 100%, resulting in 74.40% in the interpretation of the value of the good category.